2021
DOI: 10.1186/s43168-021-00072-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of pulmonary and extrapulmonary tuberculosis cases in Giza Governorate during the period of 2014–2018

Abstract: Background Tuberculosis in Egypt is a main public health problem. Egypt is categorized among the mid-level incidence countries. The objective of this work is to study the epidemiology of TB in Giza Governorate during the period from 2014 to 2018. Results This study revealed that the total number of TB cases in Giza Governorate during the period from 2014 to 2018 was 3357 (2035 males and 1322 females including 199 children) with the highest number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The mean age of those patients was 46.81 years with range between 30 and 62 years. In consistent with the current study, Malik et al (2021) stated that the majority of cases with TB occurred between 18 and 65 years [21]. Unlike Yang et al (2019) who reported that bronchiectasis was more prevalent at the age of 40 or older [22], it was found that age of those with bronchiectasis was insignificantly lower than those without bronchiectasis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mean age of those patients was 46.81 years with range between 30 and 62 years. In consistent with the current study, Malik et al (2021) stated that the majority of cases with TB occurred between 18 and 65 years [21]. Unlike Yang et al (2019) who reported that bronchiectasis was more prevalent at the age of 40 or older [22], it was found that age of those with bronchiectasis was insignificantly lower than those without bronchiectasis.…”
Section: Discussionsupporting
confidence: 87%
“…It was found that those patients had significantly younger age in comparison to those without DRTB (32.5 ± 1.73 vs. 47.52 ± 7.98 years; p< 0.001) and all of them had liver disease. This study had high percentage of DRTB in comparison to Abd El Malik et al (2021) [21] who found out 20/3357 (0.59%) patients had DRTB. Moreover, there was no statistical difference between DRTB prevalence in patients with and without bronchiectasis.…”
Section: Discussionmentioning
confidence: 53%
“…Tuberculosis (TB) is still a global health problem especially in developing countries, where it results in a high morbidity and mortality [ 1 ]. The problem is exaggerated by the increasing prevalence of drug-resistant tuberculosis (DR-TB), in which the treatment is characterized by high cost, longer time, lower effectiveness, and more side effects [ 2 ].…”
Section: Introductionmentioning
confidence: 99%